If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3) = 2(4x + 1) Reorder the terms: (-3 + 2x) = 2(4x + 1) Remove parenthesis around (-3 + 2x) -3 + 2x = 2(4x + 1) Reorder the terms: -3 + 2x = 2(1 + 4x) -3 + 2x = (1 * 2 + 4x * 2) -3 + 2x = (2 + 8x) Solving -3 + 2x = 2 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -3 + 2x + -8x = 2 + 8x + -8x Combine like terms: 2x + -8x = -6x -3 + -6x = 2 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + -6x = 2 + 0 -3 + -6x = 2 Add '3' to each side of the equation. -3 + 3 + -6x = 2 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = 2 + 3 -6x = 2 + 3 Combine like terms: 2 + 3 = 5 -6x = 5 Divide each side by '-6'. x = -0.8333333333 Simplifying x = -0.8333333333
| 4(x-6)=52 | | 24=(2x)-(3x-1) | | 0.8x=0.16 | | 1.5x^2+3x-12=0 | | -3(a+5)-10(1-6a)= | | 11x+8=1x+48 | | 6(a-2b)-3(2a+b)= | | 0.16xn=74 | | (7x+6)-(-8x+9)= | | -2x-13=6 | | 3.5x(2x+3)-3x(x+1.5)= | | 1000z^3-1=0 | | 6-5p=-7p+3p | | 3(-2-3x)=-8x-4 | | y+0.4=0.6y+1.2 | | -128-8y=-48 | | 5n^2+5n=6 | | 5w=-5w+10w | | 2v^2-11v=v^2-14 | | 3(a-7)=21 | | 770=22w | | -20=x+7 | | 8x-9=2x+3 | | (6x+4)-(8x+8)= | | 0.7n-9+3=11-0.3n-15 | | 4g-3=-10 | | 0.5x+3=9.5 | | -4x^2-22x-10= | | 14+12x=11x-38 | | 11b=143 | | -4x-22x-10= | | 120=(2x+10)+(x+15) |